Ukuran Perusahaan, Financial leverage dan Kinerja Perusahaan di Agensi K-Pop Besar Korea Selatan - Annaya Rizha Fairy; Shabrina Sadewi; Alika Nadda; Nabila Liana (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The company’s performance is reflected in the company’s financial statement which informs the company’s current and past financial conditions to predict their future financial conditions. In improving the company’s performance, it is necessary to pay attention to internal factors by maximizing company’s existing resources or assets. The company’s performance will increase if the profitability also increases, which means that the company’s prospects are good. This will attract investors because it is considered to provide prosperity for the shareholders. This study aims to determine the effect of firm size and financial leverage on financial performance at large South Korean K-Pop agencies 2019-2021. The population in this study is 4 companies referred to as “Big 4 Entertainment Companies” in South Korea. The sampling technique used in this research is purposive sampling technique. This study has 12 observational data obtained from the total of 4 research samples. The analytical method used in this study is panel data regression analysis using SPSS software. The results of the study show that firm size and leverage have no effect on company performance at large K-pop agencies in South Korea for the period 2019 – 2021 either partially or simultaneously.